Zn–Fe–O@C hollow microspheres as a high performance anode material for lithium-ion batteries. Issue 9 (17th January 2017) - Zhao, Jiayue; Su, Junming; Liu, Siyang; Chen, Xiang; Huang, Tao; Yu, Aishui
Abstract : The uniform carbon coating that elevates electrical conductivity and improve the structural stability of the active materials. Abstract : In this study, Zn–Fe–O@C hollow microspheres are prepared by chemical vapor deposition (CVD) method with ZnFe2 O4 hollow microspheres as precursors which are synthesized via a facile solvothermal method. ZnFe2 O4 hollow microspheres and Zn–Fe–O@C hollow microspheres are characterized by X-ray diffraction, Raman spectroscopy, scanning electron microscopy and transmission electron microscopy. The physical analysis shows a fraction of Fe(iii ) reduced to Fe(ii ) and the hollow microspheres maintained during the CVD process. Zn–Fe–O@C hollow microspheres can deliver a reversible specific capacity of 1035.6 mA h g −1 after 50 cycles at a current density of 100 mA g −1, and maintain a stable capacity as high as 1000 mA h g −1 at 500 mA g −1 after 200 cycles. Compared with ZnFe2 O4 hollow microspheres, Zn–Fe–O@C hollow microspheres present excellent rate performance. The better electrochemical performances of the Zn–Fe–O@C hollow microspheres should be ascribed to the carbon coating, which can elevate electrical conductivity and improve the structural stability of the active materials.